Association between maternal lipid levels in the second trimester and preterm birth in dichorionic twin pregnancies: a retrospective study in China - Hao Ying; Shengyu Wu; Pingping Su; Yiying Huang; Wenni Zhou; Huan Han; Jiaqi Dong; Wenjiao Li (BMJ Open)
Objectives To investigate the relationship between maternal lipid levels in the second trimester and preterm birth in twins.Design A single-centre retrospective study.Setting This study was conducted between January 2019 and December 2020.Participants This retrospective study included patients with twin pregnancies who delivered at our hospital. A total of 1309 twin pregnancies were registered. According to the eligibility criteria, 745 dichorionic (DC) twin pregnancies were finally included.Primary and secondary outcome measures Maternal serum triglycerides (mTG) and total cholesterol (TC) were tested in the second trimester (18–28 weeks) and divided as low (<25th percentile), optimal (25th–75th percentile) and high (>75th percentile). A logistic regression model was performed to assess the associations of maternal TG and TC levels in the second trimester with preterm birth.Results A total of 745 DC twin pregnancies were included, with 53.56% (399/745) of preterm birth. The preterm birth group had higher mTG concentrations in the second trimester (p<0.001) than the term birth group, while TC concentrations showed no statistically significant difference between the two groups. High mTG was associated with increased risks of total preterm birth and early preterm birth (total: adjusted OR (aOR)=1.55, 95% CI: 1.05 to 2.82; early: aOR=2.01, 95% CI: 1.08 to 3.72). When TG levels were treated as a continuous variable, each TG unit increase was related to a 28% increased risk of preterm birth. In further analysis, we found that high mTG was related to a higher risk of preterm birth in women with in vitro fertilisation-embryo transfer (IVF-ET) (aOR=1.65, 95% CI: 1.04 to 2.60), especially early preterm birth (aOR=3.07, 95% CI: 1.49 to 6.31).Conclusions High mTG levels in the second trimester were positively associated with an increased risk of preterm birth, especially early preterm birth in DC twin-pregnancy with IVF-ET.